2016
DOI: 10.1007/s00784-016-1842-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geranylgeraniol on microvessel sprouting after bisphosphonate substitution in an in vitro 3D-angiogenesis assay

Abstract: Since supportive therapeutic options for BP-ONJ are lacking, GGOH might be a promising substitute for BP-ONJ prevention and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…For a long time it has been assumed that (III) intussusception has a special importance during embryonic development and is only a minor player in adults. This thesis had to be reconsidered since recent studies have demonstrated that intussusception does also have a key role in adults [ 21 , 33 , 34 ]. The current in vitro and in vivo studies strictly focused on sprouting angiogenesis from HUVEC cell spheroids in vitro or from preexisting blood vessels in murine matrigel assays in vivo [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For a long time it has been assumed that (III) intussusception has a special importance during embryonic development and is only a minor player in adults. This thesis had to be reconsidered since recent studies have demonstrated that intussusception does also have a key role in adults [ 21 , 33 , 34 ]. The current in vitro and in vivo studies strictly focused on sprouting angiogenesis from HUVEC cell spheroids in vitro or from preexisting blood vessels in murine matrigel assays in vivo [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This thesis had to be reconsidered since recent studies have demonstrated that intussusception does also have a key role in adults [ 21 , 33 , 34 ]. The current in vitro and in vivo studies strictly focused on sprouting angiogenesis from HUVEC cell spheroids in vitro or from preexisting blood vessels in murine matrigel assays in vivo [ 21 , 22 , 23 ]. The influence of bisphosphonates on special types of angiogenesis, such as intussusceptive angiogenesis, has not yet been sufficiently explored and might be an interesting topic for further studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations